PENGARUH ATRIBUT SUPERMARKET TERHADAP MOTIF BELANJA HEDONIK DAN MOTIF BELANJA UTILITARIAN SERTA LOYALITAS KONSUMEN CARREFOUR DI SURABAYA - IRSAN, YANUAR (Universitas Katolik Widya Mandala Surabaya, 2013)
This research aimed to review the effect of supermarket attributes to the hedonic shopping motives and utilitarian shopping motives and consumer loyalty. Object of this study is a Carrefour in Surabaya. The research sample is 150 people in Surabaya who ever shopping of Carrefour. The sampling technique used in this study is a non probability sampling. Meanwhile, the analysis technique is using Structural Equation Modeling (SEM) with Analysis of Moment Structure program. The study results showed that the positive effect attribute motives supermarket shopping hedonic and utilitarian motives and consumer loyalty.